Anishinaabemodaa Pane Oodenang: a qualitative study of Anishinaabe language revitalization as self-determination in Manitoba and Ontario - Pitawanakwat, Brock Thorbjorn (2009)
Anishinaabeg (including Odawa, Potawatomi, Ojibwe, Saulteaux, and Chippewa) are striving to maintain and revitalize Anishinaabemowin (the Anishinaabe language) throughout their territories. This dissertation explores Anishinaabemowin revitalization to find out its participants’ motivations, methods, and mobilization strategies in order to better understand how Indigenous language revitalization movements contribute to decolonization and self-determination. Interviews with Anishinaabe language activists, scholars, and teachers inform this investigation of their motivations and pedagogies for revitalizing Anishinaabemowin. Interviews took place in six Canadian cities as well as four reserves: Brandon, Peterborough, Sault Ste. Marie, Sudbury, Toronto and Winnipeg; Lac Seul First Nation, M’Chigeeng First Nation, Sagamok First Nation, and Sault Tribe of Chippewas Reservation. A variety of language revitalization initiatives were explored including those outside the parameters of mainstream adult educational institutions, particularly evening and weekend courses, and language or culture camps. This investigation addresses the following questions: Why have Anishinaabeg attempted to maintain and revitalize Anishinaabemowin? What methods have they employed? Finally, how does this emerging language revitalization movement intersect with other efforts to decolonize communities, restore traditional Anishinaabe governance, and secure self-determination? The study concludes that Anishinaabemowin revitalization and Anishinaabe aspirations for self-determination are interconnected and mutually-supporting goals whose realization will require social movements supported by effective community-based leadership.